Parallel genetic algorithms with simulated annealing applied to school timetabling - Calaor, Adora Espina. 1978- (2001)
This research prents a solution to the school timetabling problem using parallel genetic algorithms with simulated annealing. The hybridization of simulated annealing and parallel genetic algorithm is explained here. Also, how these algorithms are run in parallel on a local network of workstations are discussed. Some comparative results between the different sequential algorithms using genetic algorithm and simulated annealing, their hybrids, and their parallel counterparts are exhibited in this research. The implementation of the sequential and parallel algorithms is used to construct conflic-free and satisfying timetables for the Department of Mathematics of the University of the Philippines Diliman, The program output of this study can be easily modified to be used as a hlepful and efficient guide to the decision-making process of the scheduler. Keywords: parallel genetic algorithms, school timetabling, simulated annealing.